Evaluation of the therapeutic effect of hyperbaric oxygenation and erythropoietin in the treatment of chronic heart failure using myocardial perfusion scintigraphy G-SPECT - Baškot Branislav; Živković Miodrag; Tepić Sandra; Obradović Slobodan (Vojnosanitetski Pregled)
Background. The most important predictors of longterm survival in patients with cardiac ischemic disease are left ventricular ejection fraction, left ventricular volumes, infarction size, presence and extent of residual myocardial ischemia. One of the most important recent developments in single photon emission computed tomography (SPECT) myocardial perfusion imaging is the ability to acquire these studies in conjunction with electrocardiogram (ECG) gating (G-SPECT). The ability to asses radionuclide myocardial perfusion and function with ECG G-SPECT imaging has revolutionized this field of nuclear cardiology. Study with G-SPECT development algorithms permits to quantify measures of left ventricular (LV) volume, ejection fraction (LVEF) and even regional myocardial wall motion and thickening. The American Society of Nuclear Cardiology (ASNC) in its position paper from March 1999 recommends the routine incorporation of G-SPECT during cardiac perfusion scintigraphy. Case report. We presented a 70-year-old male with ischemic heart disease (dilatative, cardiomyopathy and absolute arrhythmia). He was few times hospitally treated by medicamentous therapy with no evidence of improvement. After hospital treatment, we included hyperbaric oxygenation (HBO) and erythropoietin injections. Hyperbaric oxygenation was carried out in a monoplace hyperbaric chamber, BLK S-303, by a graduated protocol for patients with severe heart insufficiency, totally 15 treatments. Recombinant erythropoietin beta (RecormonR F. Hoffmann-La Roche) was applied deeply subcutaneously, every second day from 2 000 IU to totally 16 000 IU. Before the therapy G-SPECT study was performed with 99m technetium-MIBI, and we obtained the functional parameters and perfusion of the left ventricle to follow-up the therapy effects. The study was performed by an ADAC-VERTEX PLUS-EPIC two-head gamma camera with dedicated quantitatively algorithm Auto-QUANT. The results of LVEF were 15%, with severity abnormal motion and wall thickening for all segments. Left ventricle end-diastolic volume was 393 ml (normal < 142 ml), and LV end-systolic volume was 334 ml (normal < 65 ml). Four months after the therapy G-SPECT showed improvement in any parameters; LVEF 25%, with improvement in wall motion (normalized wall motion in the anterior, lateral area, and proximal septum) and wall thickening, LV end-diastolic volume was 390 ml, LV end-systolic volume was 289 ml. Conclusion. Using G-SPECT method before and after the therapy with hyperbaric oxygenation and erythopoietine we obtained objective improvement and good therapy effects in the treatment of chronic heart insufficiency.